Effect of Sludge on Properties of Concrete by Partial Replacement of Fine Aggregate - Gangarde Abhijeet,; Khan Tanaiya,; Somvanshi Pranav,; Sonawane Samiksha,; Khedkar Vishal,; Dr. Gunaware P. D,; Prof. Pachpute A. B, (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Now a day’s good quality natural river sand is not readily available. It is to be transported from a long distance. These resources are also exhausting very rapidly. So, there is a need to find alternative to natural river sand. Natural river sand takes millions of years for its formation and is not renewable. As a substitute to natural sand, artificial sand is used as a complete replacement. The rapid increase in construction activities leads to scarcity of conventional construction materials such as cement, fine aggregate and coarse aggregate. Researches are being conducted for finding cheaper materials. In India, there are many waters treatment plant WTP sludge which leads in problems of disposal. The final destination of water treatment plant sludge affects the environment. The experimental work is mainly concern with the study of different properties like compressive strength, split tensile strength and as well as flexural strength of concrete by partial replacement of River sand by sludge as fine aggregate. Tests over carried out on cubes, cylinders to studies the different properties concrete using sludge and compare with concrete with natural sand as fine aggregate. Rivers and was replaced with four percentages (0%, 5%, 10%, 15%) of sludge by weight. A concrete mix proportions are made with and without sludge. Compression test, splitting tensile strength test and flexural strength test were carried out to evaluate the strength properties of concrete at the age of 7, 14 &28 days. Acid attack test, Electrical Conductivity test and non-destructive test can be carried out to age of 28 days of concrete using ambient curing.
Keywords: WTP sludge; Coarse Aggregate; Compressive Strength